KEMANDIRIAN PONDOK PESANTREN SUNAN PANDANARAN YOGYAKARTA DAN RELEVANSI DENGAN EDUCATION FOR SUSTAINABLE DEVELOPMENT - Khotijah, Lia Nur; Mushawir, Mushawir (Journal of Innovation Research and Knowledge, 2024)
Pesantren currently also has the responsibility to develop and empower it in all fields including economic aspects, changing the technique of preaching which used to be quite using the oral method to become a matter of practice in the midst of increasing community problems by deepening the religious and economic fields. This is what drives a number of pesantren to try to combine the religious education system with entrepreneurial training. With a sustainable education system and entrepreneurial development, students will be accustomed to solving problems around them. The purpose of this study is to find out how the role of the Sunan Pandanaran Islamic Boarding School in Sustainable Development of Education, to find out the independence of the Sunan Pandanaran Islamic Boarding School in Yogyakarta and its relevance to education for sustainable development. The research conducted uses qualitative descriptive research with a case approach. The results of the research in the independence program of the Hajar Aswad Pandanaran branch of the Islamic boarding school include: Pandanaran Green House Aquaponics to integrate fish and vegetable cultivation at the Pandanaran Islamic Boarding School, Bustan Nursery (Environmental awareness (Natural resource conservation and waste reduction, Plastic Waste Bottle Management), Taman Mini Zoo, Women's Empowerment Program, Hajar Aswad Islamic Boarding School Cooperative. The application of the four principles of EFSD, namely the Principle of Centralized and Intergenerational Justice at the Hajar Aswad Boarding School, the Principle of caution, the Principle of paying attention to environmental impacts, the principle of sustainable benefits are: Having been able to be independent in human resources and having been able to be independent in financing/finance